2010
DOI: 10.1111/j.1468-2958.2009.01366.x
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Lying in America: Three Studies of Self-Reported Lies

Abstract: This study addresses the frequency and the distribution of reported lying in the adult population. A national survey asked 1,000 U.S. adults to report the number of lies told in a 24-hour period. Sixty percent of subjects report telling no lies at all, and almost half of all lies are told by only 5% of subjects; thus, prevalence varies widely and most reported lies are told by a few prolific liars. The pattern is replicated in a reanalysis of previously published research and with a student sample. Substantial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
292
2
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(322 citation statements)
references
References 33 publications
24
292
2
4
Order By: Relevance
“…550 per person per year), although the distribution was highly skewed (23% of all lies were told by 1% of individuals, and half of all lies were told by 5% of the respondents) [32]. A number of other studies have reported frequencies between 0.6-2.0 lies per day, with lies being less common in face-to-face interactions than in telephone interactions [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…550 per person per year), although the distribution was highly skewed (23% of all lies were told by 1% of individuals, and half of all lies were told by 5% of the respondents) [32]. A number of other studies have reported frequencies between 0.6-2.0 lies per day, with lies being less common in face-to-face interactions than in telephone interactions [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…People lie, on average, once or twice per day (DePaulo, Kirkendol, Kashy, Wyer, & Epstein, 1996; but see Serota, Levine, & Boster, 2010). Lying is generally considered an antisocial behavior, and most human cultures have some prohibition against lying.…”
mentioning
confidence: 99%
“…considerar el hecho, ya largamente documentado, donde es común que los individuos contesten de forma equivocada a los cuestionarios de surveys, o mientan sobre todo en asuntos sensibles (Jonhson & Van De Vijver, 2003, Tourangeau & Yan, 2007Serota, Levine & Boster, 2010), el Google Trends ofrece una manera segura de vencer ese obstáculo, ya que la frecuencia generada por un término o conjunto de términos representa con alta fiabilidad el interés en el mundo real (Choi &Varian, 2012;Horak, Ivan, Kukuliaã, Inspektor, & Devecka, 2013).…”
Section: Ideología Y Mujeres En Los Parlamentosunclassified